GEOGRAPHIC INFORMATION SYSTEMS FOR ASSESSMENT OF CLIMATE CHANGE EFFECTS ON TEFF IN ETHIOPIA - YUMBYA, J; VAATE, BIJ DE; KIAMBI, D; KEBEBEW, F (African Crop Science Journal, 2014)
The value of Geographic Information Systems (GIS) for assessing climate change impacts on crop productivity cannot be over-emphasised. This study evaluated a GIS based methodology for teff (Eragrostis tef) production in Ethiopia. We examined the spatial implications of climate change on areas suitable for teff, and estimated the effects of altered environments on teff’s productivity. There was a non-linear relationship between suitability indices, the output of spatial analysis and teff yield data collected from diverse ecological zones. This served as the basis for country-wide crop yield analysis for both current and future climate scenarios. To complement this effort, a socio-economic survey was carried with a thrust of understanding the agricultural activities in the study area. With the current climatic conditions, 87.7% of Ethiopia is suitable for teff. On the other hand, approximately 67.7% of Ethiopia is expected to be suitable for teff production by 2050. Suitability index (SI) and the actual crop yield data showed a strong positive correlation (r = 74%). There is a predicted severe drop in teff yield (-0.46t ha-1) by the year 2050. Based on the current area under teff in Ethiopia, this equals an overall reduction in national production of about 1,190,784.12 t, equivalent to a loss of US$ 651 million to farmers. The results indicate that crop yield varied significantly as a function of climatic variation and that the model is applicable in assessing the impact of climate change on crop productivity at various levels taking into consideration spatial variability of climate.
Keywords: Climate change, suitability index, teff